Abundance of sucking insect pests on some flowering plants in relation to weather parameters - Amin, MR; Islam, MA; Afroz, M; Suh, SJ (Bangladesh Journal of Scientific and Industrial Research, 2021)
The study was conducted from November 2017 to May 2018 in the experimental field at Gazipur, Bangladesh to investigate the incidence of sucking pests namely gladiolus thrips Teniothrips simplex, tuberose aphid Aphis craccivora, marigold aphid Neotoxoptera oliveri, and dahlia mealybug Plannococcus citri on their cultivated host plants in relation to temperature, relative humidity and rainfall. Results showed that the abundance of gladiolus thrips, tuberose aphid, marigold aphid and dahlia mealy bug reached the peak in the 3rd week of January, 3rd week of February, 1st week of January and 1st week of February, respectively. Among the weather factors, temperature had significant negative impact on the abundance of gladiolus thrips, marigold aphid and tuberose aphid, whereas rainfall showed significant negative influence only on marigold aphid. Multiple linear regression analysis showed that weather variables collectively predicted 55.9%, 75.9%, 44.5%, and 34.6% abundances of gladiolus thrips, marigold aphid, tuberose aphid and dahlia mealybug, respectively. Bangladesh J. Sci. Ind. Res.56(4), 241-248, 2021